Indonesian High School Students’ Reading Strategies in Foreign Language Learning - Sugeng Susilo Adi (Fakultas Ilmu Budaya, Universitas Brawijaya, 2020)
This article aims at finding out the reading strategies used by Indonesian 10th graders. This research uses survey in collecting data. To achieve the objectives, 104 questionnaires were administered to all participants. The researcher used mean as the measurement to determine the category of usage level for each category of reading strategy. The survey questionnaires are those developed by Mokhtari and Sheorey (2002) named Survey of Reading Strategies (SORS). The reading strategies here are based on the SORS questionnaire which is global reading strategies, problem solving strategies, and support strategies. The research found that students’ usage on reading strategies is high with students’ preference of problem solving strategies. Some suggestions are made by the researchers regarding with the finding and discussion of this study. The suggestions are made for the English teacher which can help them to enhance the student’s learning better, as for the students can make them know about how to apply reading strategies used by them well, and also for the next researcher that have similarities with this study can use this study as the reference or as an introductory research.